Avaliação farmacocinética de duas formulações de norfloxacino em voluntários sadios de ambos os sexos - Moraes, Renata Amaral de (2010)
The pharmacokinetic profile of two different formulations of Norfloxacin tablets - 400 mg; as test formulation versus Floxacin®, Norfloxacin reference formulation (- 400 mg; Merck Sharp & Dohme) was evaluated in 32 healthy volunteers of both sexes. The research was consisted of an open, randomized, crossover study, designed with two treatments, two periods (two sequences) with a minimum interval of seven days (washout) between the admissions. Blood samples were collected at regular intervals to construct the plasma concentration versus time curves. The concentrations of Norfloxacin were analyzed by High Performance Liquid Chromatography coupled to Mass Spectrometry (HPLC-MS/MS). The geometric mean of test Norfloxacin / reference Norfloxacin and confidence interval (CI) of 90% for Cmax and AUC0-t last were 103.9020% (89.5247 to 120.5881%) and 99.3030% (87.8186 - 112.2892%) respectively. Whereas the studied formulations showed the ratio between the mean Cmax and AUC0-t last between 80 and 125%, considering a confidence interval of 90%, as proposed by the Food and Drug Administration and ANVISA, it appears that the two formulations of Norfloxacin showed similar bioavailability in rate and in extent of absorption.